Mastering priorities - Frohman, Mark (Collaborative leader., 2000)
Offers a comprehensive, easy-to-use tool that helps you clearly lay out your priorities and translate them into an action plan. This "Priority Matrix" helps you to schedule appropriate time for each task, spread out work based on well-thought-out priorities, and realistically assess obstacles, organizational land mines, and "people tripwires"--all in minutes.